2006
DOI: 10.1038/oby.2006.247
|View full text |Cite
|
Sign up to set email alerts
|

A Visfatin Promoter Polymorphism Is Associated with Low‐Grade Inflammation and Type 2 Diabetes

Abstract: visfatin promoter polymorphism is associated with low-grade inflammation and type 2 diabetes. Obesity. 2006;14: 2119 -2126. Visfatin (also known as pre-B cell colony-enhancing factor, or PBEF) is a pro-inflammatory adipokine expressed predominantly in visceral fat. We investigated whether polymorphisms at the visfatin/PBEF locus influence the risk of type 2 diabetes (T2D). Linkage disequilibrium analysis of 52 single nucleotide polymorphisms spanning the entire gene (34.7 kb) plus 20.5 kb of the upstream regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
2
56
3
Order By: Relevance
“…Although this study was retracted in 2007 due to numerous scientific flaws, the original observation was supported by a number of subsequent studies demonstrating that plasma visfatin levels in humans correlate with obesity, visceral fat mass, type 2 diabetes, and presence of the metabolic syndrome (171)(172)(173). Furthermore, visfatin promoter SNPs were reported to be associated with fasting glucose and insulin levels, as well as type 2 diabetes (174,175). Other studies, however, did not confirm an association of visfatin and visceral adipose tissue or parameters of insulin sensitivity in humans and rodents (176)(177)(178)(179).…”
Section: Visfatin/pbef/namptmentioning
confidence: 74%
“…Although this study was retracted in 2007 due to numerous scientific flaws, the original observation was supported by a number of subsequent studies demonstrating that plasma visfatin levels in humans correlate with obesity, visceral fat mass, type 2 diabetes, and presence of the metabolic syndrome (171)(172)(173). Furthermore, visfatin promoter SNPs were reported to be associated with fasting glucose and insulin levels, as well as type 2 diabetes (174,175). Other studies, however, did not confirm an association of visfatin and visceral adipose tissue or parameters of insulin sensitivity in humans and rodents (176)(177)(178)(179).…”
Section: Visfatin/pbef/namptmentioning
confidence: 74%
“…Chronic low-grade inflammation constitutes a mediator in the development of obesity-related diseases. The association of NAMPT with other inflammatory markers, such as MCP-1 and PAI-1 antigen [57] together with its increased production and release by macrophages [28,58] supports its pro-inflammatory properties [59]. Furthermore, a strong association between NAMPT and TNF-a and IL-8 in PBC has been described [39,46,58].…”
Section: Discussionmentioning
confidence: 88%
“…Our studies identified two ARDSassociated NAMPT promoter SNPs (22,422A/G and 2948G/T), and, despite study limitations, including relatively small groups of patients with ARDS and controls and lack of cross validation in the two ARDS cohorts, our in vitro experiments confirmed robust and significant influence of these SNPs on NAMPT promoter activity in response to 18% CS challenge. Functionality of the 2948G/T (C/A) variant is supported by recent studies associating this NAMPT SNP with low-grade inflammation in patients with diabetes (31). Under static conditions, silencing of STAT5 failed to influence the activity of promoters with 22,422A/G or 2948G/T.…”
Section: Discussionmentioning
confidence: 90%